ECONOMIC ANALYSIS OF MARKETING SYSTEM OF POTATO IN KANGRA DISTRICT OF HIMACHAL PRADESH - Sharma, Vikalp (Potato Journal, 2018)
Potato J (2017) 44 (2): 89-94 ECONOMIC ANALYSIS OF MARKETING SYSTEM OF POTATO IN KANGRA DISTRICT OF HIMACHAL PRADESH Vikalp Sharma1 , Harbans Lal1 and Divya Sharma1 ABSTRACT: Potato is one of the principal cash crop grown in Himachal Pradesh and occupies 14,685 hectares of area which is about 20% of the total area under vegetables in the state. The study is based on data collected from 60 farmers selected through proportional allocation from selected villages of two blocks namely Bhawarna and Nagrota Bagwan. The marketable surplus of potato accounted for nearly 94% of its total production. The total production, losses and family size turned out to be most important factors affecting the marketed surplus of potato. The channel-IV involving local traders, commissionagent-cum-wholesalers, retailers and consumers were the most important channel. The producer’s share in consumer’s rupee was highest in Channel-I (92.61%) where the farmers sold potato directly to the consumers. The channel-IV (involving producers, local traders, wholesalers, retailers, consumers) was found to be most efficient and prominent in the study area from the view point of higher net price received by farmers and higher marketing efficiency index.